AN ANSELMIAN METHOD FOR CONTEMPORARY SOTERIOLOGICAL DEBATES - Evans Winata; Jonathan Octavianus (CV Naskah Aceh, 2026)
Reformed Epistemology successfully defends the rationality of Christian belief against evidentialist objections. Plantinga demonstrates that belief in God can be properly basic and warranted without inferential justification. But this apologetic achievement leaves a methodological gap: believers know they are rational to believe, yet lack rigorous tools for adjudicating between competing doctrines. Both Calvinist and Arminian can claim warranted beliefs about salvation; Reformed Epistemology offers no criteria for choosing between them. This paper argues that Anselm's fides quaerens intellectum fills precisely this gap. Beginning with faith and deploying reason to explore internal coherence, Anselmian method provides constructive theological tools that complement Reformed Epistemology's defensive posture. Three case studies demonstrate the method's utility: the logical order of salvation, the relationship between justification and sanctification, and the grounds of assurance. In each case, Anselmian analysis clarifies underlying commitments, reveals logical structures, and enables more productive theological dialogue. The paper concludes that this medieval method addresses a critical need in contemporary evangelical thought—transforming apologetic defense into constructive systematic theology.